Brassica incana Ten. (Brassicaceae): Phenolic Constituents, Antioxidant and Cytotoxic Properties of the Leaf and Flowering Top Extracts - Miceli, Natalizia (Molecules, 2020)
Brassica incana Ten. is an edible plant belonging to the Brassicaceae family. In this work, the phenolic composition and the antioxidant and cytotoxic properties of the hydroalcoholic extracts obtained from the leaves and the flowering tops of B. incana grown wild in Sicily (Italy) were studied for the first time. A total of 17 and 20 polyphenolic compounds were identified in the leaf and in the flowering top extracts, respectively, by HPLC-PDA-ESI-MS analysis. Brassica incana extracts showed in vitro antioxidant properties; the leaf extract displayed greater radical scavenging activity in the 2,2-diphenyl-1-picrylhydrazyl (DPPH) test than the flowering top extract (IC(50) = 1.306 ± 0.049 mg/mL and 2.077 ± 0.011 mg/mL), which in turn had a stronger ferrous ion chelating ability than the other (IC(50) = 0.232 ± 0.002 mg/mL and 1.147 ± 0.016 mg/mL). The cytotoxicity of the extracts against human colorectal adenocarcinoma (CaCo-2) and breast cancer (MCF-7) cell lines was evaluated through the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and the lactic dehydrogenase (LDH) release determination. The extracts showed cytotoxic efficacy against Caco-2 cells, with the flowering top extract being the most effective (about 90% activity at the highest concentration tested). In the brine shrimp lethality bioassay, the extracts exhibited no toxicity, indicating their potential safety.